Logika Hukum Putusan Mahkamah Konstitusi Terkait Uji Konstitusional Undang-Undang Jabatan Notaris - Iskandar Muda (Jurnal Konstitusi, 2020)
Settlement of the problem of testing the law in the Constitutional Court (constitutional review) is also needed to find out the logic of the law and its relationship. If two statements are displayed simultaneously it will give rise to what by logic is called “logic relationship.” In the settlement of the six cases of constitutional review of the law on the Position of Notary Public (Law No. 30 Year 2004) and its Amendments (Law No. 2 Year 2014) revealed the use of various kinds of legal logic in legal considerations (ratio decidendi) of the Court. This research is a legal research using normative approach. The results showed that: (i) Constitutional Court Decision No. 009-014/PUU-III/2005 uses the legal logic of “equivalence relations,” (ii) Constitutional Court Decision No. 52/PUU-VIII/2010 uses the legal logic of “independent relationship,” (iii) Constitutional Court Decision No. 49/PUU-X/2012 uses the legal logic of “contradictory relationship,” (iv) Constitutional Court Decision No. 72/PUU-XII/2014 uses the legal logic of “independent relationship,” (v) Constitutional Court Decision No. 43/PUU-XV/2017 uses the legal logic of “independent relationship,” and (vi) in Constitutional Court Decision No. 22/PUU-XVII/2019 uses the legal logic of “contradictory relationship.”